COVID-19 Vaccine ChAdOx1-S [recombinant] : 26 February 2021 (World Health Organization, 2021)
The ChAdOx1-S/nCoV-19 [recombinant] vaccine is a replication-deficient adenoviral vector vaccine against coronavirus disease 2019 (COVID-19). The vaccine expresses the SARS-CoV-2 spike protein gene, which instructs the host cells to produce the protein of the S-antigen unique to SARS-CoV-2, allowing the body to generate an immune response and to retain that information in memory immune cells. Efficacy shown in clinical trials in participants who received the full series of vaccine (2 doses) irrespective of interval between the doses was 63.1%, based on a median follow-up of 80 days, but tended to be higher when this interval was longer. The data reviewed at this time support the conclusion that the known and potential benefits of ChAdOx1-S/nCoV-19 [recombinant] vaccine outweigh the known and potential risks.
Keywords: vakcinace; veřejné zdravotnictví; Vaccination; infekční lékařství; COVID-19 Vaccines; preventivní medicína; vakcíny proti COVID-19; COVID-19